An updated review on the stability of anthocyanins regarding the interaction with food proteins and polysaccharides. Issue 5 (26th August 2022) - Zang, Zhihuan; Tang, Siyi; Li, Zhiying; Chou, Shurui; Shu, Chi; Chen, Yi; Chen, Wei; Yang, Shufang; Yang, Yiyun; Tian, Jinlong; Li, Bin
Abstract : Abstract: The health benefits of anthocyanins are compromised by their chemical instability and susceptibility to external stress. Researchers found that the interaction between anthocyanins and macromolecular components such as proteins and polysaccharides substantially determines the stability of anthocyanins during food processing and storage. The topic thus has attracted much attention in recent years. This review underlines the new insights gained in our current study of physical and chemical properties and functional properties in complex food systems. It examines the interaction between anthocyanins and food proteins or polysaccharides by focusing on the "structure–stability" relationship. Furthermore, multispectral and molecular computing simulations are used as the chief instruments to explore the interaction's mechanism. During processing and storage, the stability of anthocyanins is generally influenced by the adverse characteristics of food and beverage, including temperature, light, oxygen, enzymes, pH. While the action modes and types between protein/polysaccharide and anthocyanins mainly depend on their structures, the noncovalent interaction between them is the key intermolecular force that increases the stability of anthocyanins. Our goal is to provide the latest understanding of the stability of anthocyanins under food processing conditions and further improve their utilization in food industries. Practical Application : This review provides support for the steady‐state protection of active substances.